2006
DOI: 10.1158/0008-5472.can-05-4505
|View full text |Cite
|
Sign up to set email alerts
|

Shh Pathway Activity Is Down-Regulated in Cultured Medulloblastoma Cells: Implications for Preclinical Studies

Abstract: Gene expression profiling indicates that the Sonic Hedgehog (Shh) pathway is active in f30% of human medulloblastomas, suggesting that it could provide a useful therapeutic target. Previously, we showed that spontaneous medulloblastomas in Ptc1 +/À p53 À/À mice could be eradicated by treatment with a small-molecule inhibitor (HhAntag) of Smoothened (Smo).Here, we compared the responses of mouse medulloblastoma cells propagated in flank allografts, either directly or after culture in vitro, to HhAntag. We found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
126
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 29 publications
13
126
2
2
Order By: Relevance
“…In addition, other downstream pathway activation mechanisms have been revealed, such as REN deletions (15), GLI gene amplifications (24)(25)(26), GLI1 chromosomal translocations (27), or GLI2 protein stabilization (28). Moreover, reports on frequent cyclopamine-insensitivity of GLI1-positive cell lines derived from pancreatic adenocarcinoma can be found in the literature (6).…”
mentioning
confidence: 99%
“…In addition, other downstream pathway activation mechanisms have been revealed, such as REN deletions (15), GLI gene amplifications (24)(25)(26), GLI1 chromosomal translocations (27), or GLI2 protein stabilization (28). Moreover, reports on frequent cyclopamine-insensitivity of GLI1-positive cell lines derived from pancreatic adenocarcinoma can be found in the literature (6).…”
mentioning
confidence: 99%
“…shown that vismodegib could induce complete regression of tumors (40,41). Importantly, in both the autochthonous and allograft models, it was demonstrated that the near complete (39,42).…”
Section: Preclinical Efficacy Modelsmentioning
confidence: 94%
“…Таким образом, культивирование клеток на среде с сывороткой может приводить к инактивации пути HH [50,51,57]. Аналогичные данные получены и для клеток медуллобластомы, теряющих GLI активность в экспериментах in vitro [58].…”
Section: изменения сигнального пути Hedgehog при глиомахunclassified